Terpenoid trans‐caryophyllene inhibits weed germination and induces plant water status alteration and oxidative damage in adult Arabidopsis. (6th June 2016) - Araniti, F.; Sánchez‐Moreiras, A. M.; Graña, E.; Reigosa, M. J.; Abenavoli, M. R.
Abstract: trans ‐Caryophyllene (TC) is a sesquiterpene commonly found as volatile component in many different aromatic plants. Although the phytotoxic effects of trans ‐caryophyllene on seedling growth are relatively explored, not many information is available regarding the phytotoxicity of this sesquiterpenes on weed germination and on adult plants. The phytotoxic potential of TC was assayed in vitro on weed germination and seedling growth to validate its phytotoxic potential on weed species. Moreover, it was assayed on the metabolism of Arabidopsis thaliana adult plants, through two different application ways, spraying and watering, in order to establish the primary affected organ and to deal with the unknown mobility of the compound. The results clearly indicated that TC inhibited both seed germination and root growth, as demonstrated by comparison of the ED50 values. Moreover, although trans ‐caryophyllene‐sprayed adult Arabidopsis plants did not show any effect, trans ‐caryophyllene‐watered plants became strongly affected. The results suggested that root uptake was a key step for the effectiveness of this natural compound and its phytotoxicity on adult plants was mainly due to the alteration of plant water status accompanied by oxidative damage.